DYNAMICS OF STUDENTS’ PSYCHOLOGICAL WELL-BEING - Kalvāns, Ēriks (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This scientific article reflects the results of research on the psychological well-being of students of Rēzekne Academy of Technologies in 2019 and 2023. The need for such studies is justified by recent studies in various countries, which show that the prevalence and severity of mental problems among young people is increasing. Taken together, these studies show that students are increasingly experiencing symptoms of increased anxiety and stress, as well as depression. Thus, the deterioration of students' psychological well-being is a major challenge in modern universities. The aim of the empirical study: to reflect the dynamics of the level and content of the psychological well-being of young students. The analysis of scientific literature and empirical results is used as a basic method in the development of the article.